Intra-ovarian inflammatory states and their associations with embryo quality in normal-BMI PCOS patients undergoing IVF treatment - Jie Shang; Siyu Wang; Aiyuan Wang; Fang Li; Jing Zhang; Jin Wang; Rui Lv; Haixia Chen; Xiaohuan Mu; Kai Zhang; Xiaohong Bai; Ye Tian (BMC, 2024)
Abstract Background Polycystic ovary syndrome (PCOS) is the main cause of anovulatory infertility in women of reproductive age, and low-grade chronic inflammation plays a key role in the occurrence and development of PCOS. However, obesity, as a likely confounding factor, can affect the inflammatory state of PCOS patients. Objective The aim of this study was to comprehensively investigate intra-ovarian inflammatory states and their impact on embryo quality in PCOS patients with a normal BMI undergoing IVF treatment. Methods DIA-mass spectrometry-based proteomics and bioinformatic analysis were combined to comprehensively profile the protein expression of granulosa cells (GCs) from 5 normal-BMI PCOS patients and 5 controls. Thirty-four cytokines were further systematically detected in follicular fluid (FF) from 32 age- and BMI-matched normal-BMI patients using Luminex liquid chip suspension technology. Next, the differentially expressed cytokines were evaluated by enzyme-linked immunosorbent assay (ELISA) in 24 newly recruited subjects, and the relationship between these cytokines and embryo quality in PCOS patients was analysed. Finally, these cytokine levels were compared and evaluated in PCOS patients with different androgen levels. Results Proteomic analysis showed that the suppression of substance metabolism and steroid biosynthesis, more interestingly, resulted in an enhanced immune and inflammatory response in the GCs of normal-BMI PCOS patients and prompted the involvement of cytokines in this process. Luminex analysis further showed that FF macrophage inflammatory protein-1 beta (MIP-1β) and stromal cell-derived factor-1 alpha (SDF-1α) levels were significantly increased in normal-BMI PCOS patients compared to controls (P = 0.005; P = 0.035, respectively), and the ELISA results were consistent with these findings. Besides, FF MIP-1β showed an inverse correlation with the number of D3 good-quality embryos and the good-quality blastocyst rate in patients with PCOS (P = 0.006; P = 0.003, respectively), which remained significant after correction for multiple comparisons. Moreover, SDF-1α levels had no relationship with embryo development in PCOS patients. Additionally, SDF-1α levels were significantly lower in PCOS patients with high androgen levels than in controls (P = 0.031). Conclusions Local ovarian inflammation was present in normal-BMI PCOS patients, affecting follicular development, and FF MIP-1β may be a potential biomarker associated with embryo quality in normal-BMI PCOS patients. Graphical abstract